2010
DOI: 10.4149/neo_2010_04_316
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of topoisomerases enhances apoptosis in melanoma cells

Abstract: The cytotoxicity of topoisomerase I inhibiting camptothecin, topoisomerase II inhibiting etoposide and their combination were investigated in wild type p53 Bowes and mutant p53 SK-MEL-28 melanoma cell lines during 24h. A combination of camptothecin and etoposide (1 μg/ml + 10 μg/ml) proved to be efficient in both types of cell lines, although mutant p53 cells exhibited a higher resistance. Further studies proved that in Bowes cells, a combination of drugs induced p53-dependent mitochondrial apoptosis character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Other studies have indicated that SK1 is downregulated by genotoxic stress and proteolysis of p53 induced by caspases (27,28). The resistant melanoma cell line, SK-Mel-28, harbors a p53 mutation, and cell death induced by anticancer drugs is independent of p53 (29). In the present study, the expression of SK1, but not that of SK2, in the SK-Mel-28 cells was reduced following treatment with a combination of FTY720 and cisplatin, but not following treatment with cisplatin or FTY720 alone (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have indicated that SK1 is downregulated by genotoxic stress and proteolysis of p53 induced by caspases (27,28). The resistant melanoma cell line, SK-Mel-28, harbors a p53 mutation, and cell death induced by anticancer drugs is independent of p53 (29). In the present study, the expression of SK1, but not that of SK2, in the SK-Mel-28 cells was reduced following treatment with a combination of FTY720 and cisplatin, but not following treatment with cisplatin or FTY720 alone (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the interaction between FTY720 and the S1P 1 receptor blocks STAT3 signaling in B-cell lymphoma (30) and the FTY-720-induced apoptosis of renal cancer cells is mediated by the inhibition of ERK activation (13). Apoptosis induced by chemotherapeutic agents in SK-Mel-28 cells is mediated by the activation of stress kinases, such as p38 MAP kinase and SAPK/JNK (29), and by the increased expression of the transactivation factor, E2F-1 (31). Furthermore, accumulating evidence suggests that the PI3K/Akt pathway is related to chemoresistance, mainly through escape from apoptosis, and these signaling pathways promote cell survival and proliferation (32).…”
Section: Discussionmentioning
confidence: 99%
“…Drug-induced DC apoptosis control was set up by culturing DCs alone with the apoptosis-inducing topoisomerase inhibitors camptothecin (10 μM) and etoposide (1 μM) (30,31) in the absence or presence of Z-VAD-FMK. Inhibitors were purchased from Calbiochem (Gibbstown, NJ) or Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…It has been targeted by various inhibitory chemotherapeutic agents such as camptothecin and its derivatives, which inhibit Topo I, and doxorubicin, etoposides, mitoxantrone which inhibit Topo II. 36,37 In melanoma, etoposide resistance has been associated both with mutation or deletion 38 and increased activity of Topo II. 39 However, Satherley et al could not establish an association of chemosensitivity with expression of Topo II in choroidal melanoma.…”
Section: Drug Resistance Mediated By Altered Enzyme Activationmentioning
confidence: 99%